2009
DOI: 10.1080/02844310802271063
|View full text |Cite
|
Sign up to set email alerts
|

Familial congenital symmastia: Ultrastructurally abnormal breast tissue

Abstract: Reports about congenital symmastia and its surgical treatment are few. We report two patients - a mother and daughter - with congenital symmastia in whom breast and fatty tissue was found to be mobile adhering poorly to the chest wall. Although histological examination showed no abnormality of the tissue bridge between the breasts, ultrastructural investigation of breast tissue (including Cooper's ligaments) showed an abnormal arrangement of collagen fibres. Satisfying aesthetic results were achieved by resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…These sutures can be inserted through small inframammary fold incision, 5,7,8 as in our presented case, periareolar incision, 3 or vertical scar mammoplasty incision. 4 However, the inframammary incision gives superior cosmetic result as it is less visible.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…These sutures can be inserted through small inframammary fold incision, 5,7,8 as in our presented case, periareolar incision, 3 or vertical scar mammoplasty incision. 4 However, the inframammary incision gives superior cosmetic result as it is less visible.…”
Section: Discussionmentioning
confidence: 98%
“…Piza-Katzer et al 5 reported 2 cases of congenital symmastia in a mother and a daughter, and they found the abnormal arrangement of collagen fibers in the breast tissue (including Cooper’s ligament) in both cases, and so, they assumed that this condition may have a familial cause.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23] This web-like soft tissue is composed of glandular tissue, subcutaneous fat, and fibrous septa in different proportions, which traverses the sternum to connect both breasts medially. [1245] Only a few case reports of congenital symmastia have been previously reported, and the knowledge of its pathophysiology, exact incidence, and ideal treatment is still insufficient. [23] Herein, we present a case of congenital symmastia with macromastia corrected with liposuction and reduction mammoplasty with good esthetic results.…”
Section: Introductionmentioning
confidence: 99%